A finanszírozási feltételek hiányának hatásai magyarországi hulladékgazdálkodási politika implementációjára - Szabó, Ferenc (Közép-Európai Közlemények, 2015)
The primary objective of implementation research is to identify the success factors of policy implementation, and the definition of the conditions that are necessary to the effective realization of strategic objectives. Among the success factors financing conditions are of crucial importance. Money itself is not enough to the successful implementation of the policies, but the lack of the necessary financial resources leads to policy failure. In general, a partial fulfilment of the conditions leads to partial success of the implementation of a given policy. Environmental policies could be possible targets of implementation research, and they are very sensitive to the financing conditions. In my paper I examine the influence of the lack of the necessary financial resources for the implementation of the new Hungarian waste management policy launched in 2013. First I discuss the theory of implementation as a framework, then I analyze the financila conditions of the new waste management policy in that framework.